Localization of the Gunpowder Residues on the Shooters’ Hands - Üner, Hüseyin Bülent; Çerkezoğlu, Ali; Şam, Bülent; Kurtaş, Ömer; Uysal, Cafer (The Bulletin of Legal Medicine, 1999)
When a firearm is discharged, certain vaporous and particulate material are expelled in the area around the firearm. Gunpowder residue particles can be identified on shooters’ hands. The purpose of this investigation was to study the distribution of the gunshot residues left on firing hands In this study shooters tired the weapon with cloth gloves. Test shots were carried out with various types of weapons and ammunition with each hands holding the weapon. Modified Griess Test was used to detect gunpowder residue particles and their distribution pattern on the cloth gloves Gunshot residues were found, especially, on the web area of the back of the shooters’ hand. Key words: Gunshot residues, Modified Griess Test.